Modelo de gestión administrativo y contable para la junta administradora de agua potable de la Comunidad de Gualsaquí. - Velásquez Novoa, Evelyn Patricia (2015)
The accounting administrative system for the Water Board Water Parish Gualsaqui fulfills the purpose of determining the current situation in which different activities develop and propose a proposal to guide its improvement. The work you put into consideration by those responsible for providing the water service to the community, consists of four chapters. The objective of this project is to contribute with ideas, concepts and guidelines that improve the administrative and financial procedures of the Administrative Board of Water "Gual Parish sHere" and thus fulfill the obligations specified by the instances of tax control and Tax. It is a decentralized and autonomous entity legally established as a nonprofit, is composed of representatives of the community which offers the service and its employees and workers, committed to seeking the integral development of its members. The research work is divided into four chapters, concatenated together and sequential in their study; The first chapter governmental accounting theories and principles, the budget in the public sector, water law and everything related to the theoretical framework underpinning. The second chapter discusses the Technical Situational Diagnosis, its history, objectives and identification of diagnostic problem on which we will work. The proposed research work described in the third chapter, here the organizational structure of the Water Board Water "Gual Parish sHere" stands corresponding to each job functions described also detailed with special emphasis procedures and records that are suggested to be used to ensure efficient internal control. The fourth chapter refers to the main impacts produced research within the program as the unit of analysis; they are social, ethical, organizational and educational culture.